COLLABORATIVE GOVERNANCE DALAM PENGENDALIAN INFLASI DAERAH PROVINSI RIAU TAHUN 2022-2023 - Sidabutar, Maria Laura Febriani; ', Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Regional inflation control is one of the main challenges in maintaining economic stability, especially in Riau Province, which has a significant contribution to the national economy. This study aims to analyze Collaborative Governance in controlling regional inflation in Riau Province during the period 2022-2023. Collaborative Governance involves cross-sector cooperation between local governments, Bank Indonesia, business actors, academics, and the community in formulating effective policies and strategies to address inflation. This research uses qualitative methods with a descriptive research type to obtain data on findings based on research needs. This qualitative approach is used to seek information from a phenomenon that occurs and is studied, namely Collaborative Governance in Controlling Regional Inflation in Riau Province for the years 2022-2023. The purpose of this research is to understand the implementation and supporting factors of Collaborative Governance in controlling inflation in the Riau Province for the years 2022-2023. In this context, the research focuses on the coordination mechanisms among stakeholders, the effectiveness of the programs implemented, and the contributions of each party in formulating and implementing inflation control strategies. In addition, the research also explores supporting factors such as joint commitment, active involvement of all parties, and institutional capacity that enable the effective implementation of policies. The research results show that the implementation of Collaborative Governance successfully reduced the regional inflation rate to 1.96%. This success is supported by several key elements, namely effective facilitative leadership, institutional design with clear rules through the Riau Governor's Decree Number 1647/XI/2022, and a collaboration process involving face-to-face dialogue, trust building, commitment, and optimal mutual understanding. In addition, supporting factors such as strong leadership, effective coordination, transparent data and information, as well as a stable macroeconomic condition also contributed to this success. However, this study also found limitations in institutional aspects, where actors from the private sector and society have not been directly involved. The results of this study provide recommendations to strengthen cross-sector collaboration and expand actor engagement to support sustainable inflation control in the future. Keywords: Collaborative, Governance, Inflation Control , Riau